Definition of CRISPR Cas12a Trans-Cleavage Units to Facilitate CRISPR Diagnostics - Lv, Hailong; Wang, Jian; Zhang, Jian; Chen, Yijian; Yin, Lei; Jin, Dian; Gu, Dayong; Zhao, Huailong; Xu, Yong; Wang, Jin (Frontiers in Microbiology, 2021)
The CRISPR diagnostic (CRISPR-Dx) technology that employs the trans-cleavage activities has shown great potential in diagnostic sensitivity, specificity, convenience and portability, and has been recognized as the next-generation diagnostic methods. However, due to the lack of standardized definition of Cas trans-cleavage enzymatic units, it is difficult to standardize the present CRISPR-Dx systems, which have undoubtedly impeded the development of the CRISPR-Dx industry. To solve the problem, we here first systematically optimized the reaction systems for Cas12a, and then defined its trans-cleavage units (transU), which we believe will be of great importance and interest to researchers in both molecular diagnostic industry and basic research. Moreover, a simple protocol was provided to facilitate a step-by-step measurement of the Cas12a transU, which can also act as a reference for the definition of the transU for other Cas proteins.